The attitudes of nonpsychiatric nurses towards mental disorders in China - Wang, Qi-Kai; Wang, Xu; Qiu, Ya-Jing; Bao, Wen-Xin; Chen, Xia-Can; Xu, Jia-Jun (Frontiers in Psychiatry, 2024)
Background: Few studies have explored the associated factors of attitudes of nonpsychiatric nurses towards mental disorders. Therefore, this study is aimed to evaluate the attitudes of nonpsychiatric nurses towards mental disorders and especially explore the association between psychiatric clinical practice and these attitudes. Methods: A total of 1324 nonpsychiatric nurses and students majoring in nursing were recruited through an online questionnaire from December 2021 to March 2022 in Sichuan Province, China. Demographic information, personal care experience, psychiatric nursing education and the Community Attitudes towards the Mentally Ill (CAMI) were collected. A higher score indicates a stigmatizing attitude in the authoritarianism and social restrictiveness (SR) subscales and a positive attitude in the benevolence and community mental health ideology (CMHI) subscales. Multivariate linear regression was employed to analyze associated factors of attitudes towards mental disorders, and hierarchical linear regression was used to analyze the association between psychiatric clinical practice and the attitudes towards mental disorders. Results: Under the control of confounders, high education level, long residence in urban and personal care experience were positively correlated with score of authoritarianism and SR (p < 0.05), and negatively correlated with score of benevolence (p < 0.05). Long residence in urban and personal care experience were negatively correlated with score of CMHI (p < 0.05). Hierarchical linear regression analysis showed that after adjusting for demographic information, psychiatric clinical practice was associated with lower score of benevolence (B = -0.09, 95%CI = -0.17 ~ -0.003, p = 0.043) and CMHI (B = -0.09, 95%CI = -0.17 ~ -0.01, p = 0.027), but the initial associations between psychiatric clinical practice and authoritarianism, SR disappeared. Conclusions: High education level, long residence in urban, personal care experience and the psychiatric clinical practice were associated with the discrimination of nonpsychiatric nurses towards mental disorders. Further exploring practical strategies to optimize the psychiatric clinical practice experience of nonpsychiatric nurses could help improve their attitudes towards mental disorders.